PERAN PEMERINTAH DESA DAN KELOMPOK MASYARAKAT DALAM KONSERVASI MANGROVE DI DESA PUTERI SEMBILAN KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS PROVINSI RIAU - Yori Amalia; Firman Nugroho; Ridar Hendri (Pelantar Press, 2026)
Mangrove forests play an important role in maintaining the balance of coastal ecosystems, but their management still faces various challenges, including in Puteri Sembilan Village, North Rupat District, Bengkalis Regency, Riau Province. This study aims to analyze the role of the village government and community groups in mangrove forest conservation and identify the supporting and inhibiting factors. The study uses a descriptive qualitative approach through in-depth interviews, observation, and documentation. Data are analyzed thematically to describe the dynamics of roles and influencing factors. The results of the study show that the village governments acts as a regulator, facilitator, and initiator in mangrove conservation. The implementation of these roles is influenced by institutional capacity, resource availability, budget management mechanisms, and coordination between levels of government. The priority of village development oriented towards the economic and infrastructure sectors also influences the integration of conservation programs into their management still faces various challenges, including in Puteri Sembilan Village, North Rupat District, Bengkalis Regency, Riau Province village planning. Meanwhile, community groups through the Forest Farmers Group have show initiative in planting, simple nurseries, and area monitoring activities. However, these activities are still developing in technical aspects and have not been integrated with the strengthening of educational and economic functions. Overall, mangrove conservation in Puteri Sembilan Village requires institutional capacity building and improved coordination to ensure more structured and sustainable management